5(a-7)=2(2a+1)

Simple and best practice solution for 5(a-7)=2(2a+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(a-7)=2(2a+1) equation:



5(a-7)=2(2a+1)
We move all terms to the left:
5(a-7)-(2(2a+1))=0
We multiply parentheses
5a-(2(2a+1))-35=0
We calculate terms in parentheses: -(2(2a+1)), so:
2(2a+1)
We multiply parentheses
4a+2
Back to the equation:
-(4a+2)
We get rid of parentheses
5a-4a-2-35=0
We add all the numbers together, and all the variables
a-37=0
We move all terms containing a to the left, all other terms to the right
a=37

See similar equations:

| 49-3w=3w+7 | | −3(2x−1)=15 | | 35x-25=15 | | 2/3-5=x+6/12 | | 3(1+6x)=5(2x-1) | | 145/5=(x+8)/5 | | 4x+1.2=4x+0.2 | | 1x+3x=5 | | 3b+(−12)=−24 | | 1/5(m+2)=3/5-m | | 1/3+x/5=16/3x^2 | | 58/x=2 | | 241=187-y | | 2x+4x=1 | | -10-(-11)=x | | 2x+4x=11x+3x=5 | | y=0.1(1.23)^8 | | 249=29-x | | 3x(x-2)=8x^2-7x | | -4.8(x-3.75)=144.4 | | x+1.62=7.57 | | u-1.79=6.6 | | 1/3+k/5=16/3k^2 | | 13x-3=49 | | y-2.1=7.61 | | y^2+2/3y=0 | | 13=8+5u | | 25=8/3v | | 4•y=96 | | -33=x/5-3 | | 1624=28(p+10) | | 5t+7=T+15 |

Equations solver categories